Microsoft Office XP (McGraw-Hill/Irwin, 2002)
The Interactive Computing Series is the Visual, Interactive way to develop and apply software skills. This Skills based approach coupled with its highly illustrated, 2 page-spread design is ideal for the intro CIS course, the self-paced course or students in non-traditional education settings.